ANALISIS KINERJA KEUANGAN DENGAN METODE ECONOMIC VALUE-ADDED: PERUSAHAAN SUBSEKTOR INDUSTRI HASIL TEMBAKAU YANG TERDAFTAR DI BURSA EFEK INDONESIA - Suci, Saraswati Nirmala (Gapenas Publisher, 2023)
Company sector on the Indonesian Stock Exchange (BEI) that is in great demand is the consumer goods industry sector. The tobacco products industry, which is part of this sector, makes quite an important contribution to the Indonesian economy in terms of state income and employment. Therefore, it is necessary to analyze the financial performance of companies in the tobacco products industry subsector as a tool to measure the performance of companies in this subsector so that it can become a consideration for investors. This research aims to analyze the financial performance of companies in the tobacco products industry subsector listed on the IDX in 2018-2022 using the Economic Value Added (EVA) method. This research use descriptive qualitative method. The entire population with four companies was used in this study. The conclusion resulting from this research is that PT Gudang Garam Tbk. and PT HM Sampoerna Tbk. has an EVA value that is always positive (>1), PT Bentoel Internasional Investama Tbk. which is always negative (<1), and PT Wismilak Inti Makmur is always positive except in 2019 which had a value of 0